A Reappraisal of Reproduction in Anadromous Alewives: Determinate versus Indeterminate Fecundity, Batch Size, and Batch Number. Issue 6 (21st October 2015) - Ganias, Konstantinos; Divino, Jeffrey N.; Gherard, Katie E.; Davis, Justin P.; Mouchlianitis, Foivos; Schultz, Eric T.
Abstract: Innovative methods for analysis of reproduction may provide more information that can be used to conserve species of concern. We present data on oocyte development, batch size, and batch number of anadromous Alewives Alosa pseudoharengus in a lake‐spawning population located in Connecticut. We sampled female Alewives as they arrived at the spawning habitat (uprunners) and females as they were leaving (downrunners). We estimated batch size by weighing all oocytes and performed image analysis on oocytes in subsamples of some ovaries, thereby estimating oocyte size‐frequency distribution to define the number of batches. We performed both whole‐mount and histological analysis on other ovaries to compare gravimetric and stereological estimates of batch size and to precisely characterize oocyte developmental stages. Uprunners had advanced oocytes at the ultimate stage of vitellogenesis and usually three additional less‐developed batches. Postovulatory follicles and oocytes that were being resorbed were prevalent in downrunners but were absent in uprunners. Females spawned at least three batches in a season; however, downrunners had nearly as many batches as uprunners in their ovaries, indicating there was continuing recruitment and maturation of fresh batches. A numerical model of oocyte growth indicated that there is sufficient time for batches recruited at the beginning of the spawning season to develop and be spawned in the same season, indicating that fecundity is indeterminate. Accurate assessments of individual reproductive performance will require detailed consideration of within‐season oocyte dynamics as opposed to relying on enumerating oocytes in prespawners. Received November 25, 2014; accepted July 13, 2015